Prevalence of vitamin D deficiency in Pakistani population - Norhasiza, Mat Jusoh; Atif Amin, Baig; Khan, M.U. (2017)
Vitamin D deficiency (VDD) has arisen as a global issue and having manifold damaging effects on human health it needs urgent attention. Vitamin D is characteristically involved in bone and mineral regulation, but its deficiency can cause many extra-skeletal problems as well such as infections, heart diseases and even cancer. Due to its high incidence all over the world VDD is now documented as a pandemic. Situation is even more worrying in Pakistan. The present study was aimed to determine the status of vitamin D levels in general population of Lahore with sufficiently large sample size. Blood samples of 5000 healthy individuals were taken after taking their consent. After extracting serum, 25(OH)D assay was performed by Electrochemiluminescence Immuno Assay (ECLIA). Results revealed that 42% of the subjects had deficient levels of vitamin D and 29% of the participants showed insufficient levels.In current study 49% of male participants and 37 % females showed deficient levels of vitamin D. No significant association was found between vitamin D deficiency and gender or age group. Vitamin D deficiency is prevalent in Pakistan in all age groups. There is a need to take immediate measures to tackle this growing public health problem. As we are blessed to have good sunny days all-round the year, by adopting simple measures and life style changes we can win the battle against vitamin D and get rid of the risks associated with vitamin D deficiency.